Perancangan Sistem Informasi Penerimaan Bantuan Alat Pertanian Sawit Berbasis Web Menggunakan Metode Waterfall - Nur, Suci Fadhilah; Amira, Nurul; Rahmi, Tiara (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The process of submitting and distributing agricultural aid at the Plantation and Livestock Office of North Sumatra Province is still carried out manually, resulting in delays in verification, data duplication, and the absence of real-time monitoring. This study aims to design a Web-Based Agricultural Aid Reception Information System as a solution to these problems. The research method used is Research and Development (R&D) with the Waterfall development model, while data were collected through observation, interviews, and documentation and analyzed using descriptive qualitative techniques. The results indicate that the proposed system is able to integrate the entire process from submission to distribution digitally and centrally, thereby improving efficiency, data accuracy, and service transparency. The limitation of this study is that the system has not been implemented in a real environment, therefore it is recommended to conduct direct implementation accompanied by evaluation using usability testing, as well as the development of automatic notification features and population data integration